The value of quantitative and a new qualitative color pattern shear wave elastography for the differentiation of ACR TI-RADS 4 or 5 category thyroid nodules measuring ≤10 mm - Yi, Ai-jiao; Yang, Wei-Wei; Cui, Xin-Wu; Dietrich, Christoph F.; Wang, Bin (Frontiers in Endocrinology, 2024)
Objective: To evaluate the diagnostic performance of quantitative shear wave elastography (SWE) and a new qualitative color pattern SWE for the differentiation of benign and malignant ACR TI-RADS 4 or 5 category thyroid nodules measuring ≤ 10mm.: From May 2020 to July 2022, a total of 237 patients with 270 thyroid nodules were enrolled, conventional ultrasound and SWE examinations were performed for each patient. Each ACR TI-RADS 4 or 5 category thyroid nodule measuring ≤ 10mm was evaluated by quantitative SWE and a new qualitative color pattern SWE. The diagnostic performance of quantitative SWE parameters, the new qualitative color pattern SWE and combination of SWE with ACR TI-RADS for the differentiation of benign and malignant ACR TI-RADS 4 or 5 category thyroid nodules measuring ≤ 10mm were evaluated and compared.Results: Among 270 thyroid nodules in 237 patients, 72 (26.67%) thyroid nodules were benign and 198 (73.33%) thyroid nodules were malignant. The qualitative color pattern SWE showed better diagnostic performance than quantitative SWE parameters.When combining the qualitative color pattern SWE with ACR TI-RADS scores, with the optimal cutoff value of the total points ≥ 8, thyroid nodules were considered as malignant. The sensitivity, specificity, accuracy and AUC were 89.90%, 56.94%, 81.11% and 0.820 (95% CI:0.768-0.864), respectively. Compared with using qualitative color pattern SWE alone, combination of qualitative color pattern SWE and ACR TI-RADS had better diagnostic performance, which was significantly different (p < 0.05).Combination of qualitative SWE color pattern and ACR TI-RADS had high sensitivity and accuracy, which might be a convenient and useful method to differentiate benign and malignant ACR TI-RADS 4 or 5 category thyroid nodules measuring ≤ 10mm, it would be helpful for management of thyroid nodules and improving prognosis.